ANALISIS VALIDASI LEMBAR KERJA PESERTA DIDIK BERBASIS REALISTIC MATHEMATIC EDUCATION - Bakri; Agustan S; Idawati (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article analyzes the validity of realistic mathematics education-based students’ worksheet. The research design used in this article is Research and Development (R&D) with a 4D development model, which is to define, design, development, and disseminate. The research subject involved 23 students from class IV. The analysis process involved three validators that consisted of two expert validators and one validator practitioner. To analyze the feasibility of students’ worksheets based on realistic mathematics education, it was used questionnaire. Based on the validity analysis, based on data instrument tested by expert and practitioner tests either in terms of design or material, it showed that students’ worksheets based on Realistic Mathematics Education were assessed with an average score of 4.3. Thus, it could be concluded that the students’ worksheets based on Realistic Mathematics Education were valid to use in learning.